2005
DOI: 10.1007/s00221-005-2222-0
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent adaptations of left and right arms to opposite visual distortions

Abstract: Previous research has shown that subjects can adapt with either arm to an opposite visual distortion, and the two adaptive states can then be used in sequence to control the respective arm. To extend this finding, we exposed the left and right arms of our subjects to opposite-directed rotations of the visual field alternately for 20 s each, and determined the time-course of adaptation, as well as aftereffects without visual feedback under uni- and bimanual conditions. Our data confirm that two adaptive states … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 32 publications
4
35
2
Order By: Relevance
“…Error rate decreased during stage 2, however, during the final block more errors were still being made by the hand which had previously performed incompatible trials. This change in error rate performance is similar to that commonly found in adaptation studies, where an initial poorer performance is found when the condition changes from the adapted non-normal, or incompatible mapping, to an opposite or normal (compatible) mapping [20,23,28,29,33]. However, this performance decrement was not apparent in reaction time performance during stage 2 and reaction time reduced when the controlresponse relationship became consistently compatible, particularly for the hand which had previously carried out incompatible trials, resulting in no negative aftereffects for response rate.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Error rate decreased during stage 2, however, during the final block more errors were still being made by the hand which had previously performed incompatible trials. This change in error rate performance is similar to that commonly found in adaptation studies, where an initial poorer performance is found when the condition changes from the adapted non-normal, or incompatible mapping, to an opposite or normal (compatible) mapping [20,23,28,29,33]. However, this performance decrement was not apparent in reaction time performance during stage 2 and reaction time reduced when the controlresponse relationship became consistently compatible, particularly for the hand which had previously carried out incompatible trials, resulting in no negative aftereffects for response rate.…”
Section: Discussionsupporting
confidence: 68%
“…Negative error rate after-effects are commonly found in adaptation studies when incompatible mappings relationships are changed to compatible [23,24]. This effect is generally short lived, as can be seen in error rate performance.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…They further proposed that the two arm controllers have independent (short term) memory resources that can be accessed by their counterpart, based on a finding that adapting to two opposing visuomotor rotations simultaneously by the two arms neither facilitates nor interferes with interlimb transfer (Wang and Sainburg 2003). This idea has been confirmed by other studies, which demonstrated that adaptations to two opposing rotations can coexist in the sensorimotor system, one for each arm (Bock et al 2005;Galea and Miall 2006).…”
Section: Discussionmentioning
confidence: 89%